Block copolymer-assisted synthesis of VO2 (B) microflowers for supercapacitor applications. Issue 100 (1st December 2021) - Kumar, Nitish; Bansal, Neetu; Salunkhe, Rahul R.
Abstract : Synthesis of phase-optimized porous VO2 (B) microflowers using a dual templating co-assembly hydrothermal approach for supercapacitor application. Abstract : Nanoporous metal oxides are appealing candidates for energy storage applications as they can interact with guest species from inner and outer surfaces, leading to improved energy and power density performance. We have synthesized VO2 (B) microflowers with a stable phase and tailored porous structures utilizing block copolymers to achieve excellent supercapacitor performance.